Clinical characteristics and prognosis analysis of acute symptomatic seizures secondary to autoimmune encephalitis - Li, Mengyun; Zhang, Qing; Wang, Xu; Tan, Bofei; Liu, Qiang (Frontiers in Neurology, 2024)
Objective This study aimed to analyze the clinical characteristics and prognosis of patients with autoimmune encephalitis (PWAE) who experienced seizures during the acute phase. Methods Clinical data were collected from 84 patients diagnosed with AE at the General Hospital of Ningxia Medical University between January 2015 and January 2023. Patients were divided into seizure and non-seizure groups. Clinical characteristics of both groups were compared, including differences between anti-NMDAR and anti-LGI1 encephalitis within the seizure group. Due to the limited sample size and to avoid overfitting, we focused on univariate logistic regression analysis to identify individual prognostic factors. Results A total of 84 patients were enrolled, with 76.19% (64/84) in the seizure group and 23.81% (20/84) in the non-seizure group. The seizure group had a longer hospital stay (p = 0.013), higher rates of impaired consciousness (p = 0.001), and more frequent intensive care unit (ICU) admission (p = 0.011). They also had higher peripheral blood neutrophil-to-lymphocyte ratio (NLR), leukocyte count, and uric acid levels (p = 0.038, p = 0.006, p = 0.020), and were more likely to show slow-wave rhythms on electroencephalography (EEG) (p = 0.031). At 2-year follow-up, there was no significant difference in prognosis between the seizure and non-seizure groups (p = 0.653), with 35.94% (23/64) of the seizure group having a poor prognosis. Status epilepticus (SE), complications, endotracheal intubation, mRS score at discharge, APE2, and RITE2 scores increased the risk of poor prognosis (OR > 1), while intensive care and albumin reduced the risk (OR < 1). Conclusion Seizures are common in the early stages of AE, with faciobrachial dystonic seizures (FBDS) characteristic of anti-LGI1 encephalitis and SE and super-refractory status epilepticus (Sup-RSE) frequently observed in anti-NMDAR encephalitis. Seizure semiology across AE subtypes lacks specificity, and no symptoms clearly distinguish immune-mediated from non-immune causes. While seizures are linked to AE severity, particularly in anti-NMDAR encephalitis, they do not appear to impact overall prognosis. SE, complications, endotracheal intubation, modified Rankin Scale (mRS) score at discharge, Antibody-Prevalence in Epilepsy and Encephalopathy (APE2) score, Response to Immunotherapy in Epilepsy and Encephalopathy (RITE2) score, intensive care, and albumin were identified as significant prognostic factors.